PENGEMBAGAN BAHAN AJAR EDUMAT (EDUKASI MATEMATIKA) BERBASIS DIGITAL PADA MATERI BANGUN DATAR SEBAGAI PENDAMPING MUATAN MATEMATIKA SD - Farihatun Nisa'; Nuhyal Ulia; Rida Fironika Kusumadewi (Jurnal Pendidikan (Teori dan Praktik), 2021)
This research focuses on developing interactive teaching materials based on digital flat shape materials. The lack of availability of teaching materials and the use of technology occurs at the elementary school level, especially in the Mathematical content of flat shape materials. The purpose of this study was to determine the characteristics and appropriateness of Edumat teaching materials for Mathematics content of grade IV SD. The method used is research and development (R&D). This development research uses the Borg and Gall model which has been modified by Sugiyono into 7 stages. Based on this, the research results obtained include: (1) Product design stage which includes potentials and problems, data collection, media making tools and product design. (2) Product results, at this stage, produce digital-based teaching materials with the format (.apk). (3) The results of product trials which include design validation that get an average score of 0.86, the criteria "Very Valid", the validation of the teacher response questionnaire instruments and students get an average score of 0.87 for the criteria "Very Valid", the results of the trial Small scale get teacher response 46 criteria "Very Good", while the results of student responses obtained an average of 43.3 criteria "Very Good", and large scale test results obtained teacher responses with the criteria "Very Good", while the results of student responses obtained results 46.7 with the criteria "Very Good". Based on the results, Edumat teaching materials are suitable for use in learning.